INSECTICIDAL EVALUATION OF Bridelia micrantha AND Dalbergia lactea AQUEOUS EXTRACTS FOR THE CONTROL OF Podagrica uniforma (Jacoby) AND Nisotra dilecta (Jacoby) (COLEOPTERA: CHYSOMELIDAE) INFESTATION ON OKRA - Jacobs Mobolade Adesina; Kayode David Ileke; Rajashekar Yallappa; Thomas Inomisan Ofuya (AGRIVITA, Journal of Agricultural Science, 2016)
Insect pest infestation is a major factor militating against okra production and farmers generally adopt synthetic insecticides for its management. A field trial was undertaken to evaluate the insecticidal potency of Bridelia micrantha and Dalbergia lactea for the management of Podagrica uniforma (Jacoby) and Nisotra dilecta (Jacoby) insect pest of okra (Abelmoschus esculentus L. Moench). The treatments consisted of aqueous leaf extracts of Bridelia micrantha and Dalbergia lactea and Cypermethrin as check; laid out in Randomized Complete Block Design and repli-cated three times. Data was collected on insect population before treatment application and 3 days after spraying of insecticides at 28, 35, 42, 56 days after planting (DAP). Yield parameters data collected were number of fruits and fruit weight. Results obtained showed that the plant extracts exhibited effectiveness in reducing the insect population and improved okra fruit yield compared to Cypermethrin. The order of effectiveness in decreasing sequence was found to be Cypermethrin ˃ D. lacteal ˃ B. micrantha. D. lacteal and B. micrantha crude extracts could be explored as promising insecticidal agents to provide valuable alternatives to chemical control of insect infestation on okra. Further study is recommended to determine the chemical constituents responsible for the plant insecticidal activity.